Advanced catalysts for hydrogen evolution reaction based on MoS2/NiCo2S4 heterostructures in Alkaline Media. (13th January 2020) - Xu, Xiaobing; Zhong, Wei; Yan, Senlin; Zhang, Lei; Liu, Guangxiang; Du, Youwei
Abstract: There are great challenges to develop and fabricate a high performance, low-cost and stable non-platinum catalyst for hydrogen evolution reaction (HER). In our study, we firstly developed a simple method to successfully fabricate a new MoS2 /NiCo2 S4 heterostructure by a two-step hydrothermal method, and studied the HER property of MoS2 /NiCo2 S4, where the as-prepared NiCo-layered double hydroxide (NiCo-LDH) was used as the precursor of NiCo2 S4 . Benefitting from the prominent synergistic effect between NiCo2 S4 and MoS2, MoS2 provided massive catalytic active edge sites, and NiCo2 S4 enhanced the conductivity of the composite. As a result, the MoS2 /NiCo2 S4 showed excellent HER catalytic activity, with a current of 10 mA cm −2  at overpotential of 94 mV for HER and a low Tafel slope of 46 mV dec −1, and good cycling stability in Alkaline Media. As well as, our work offered one promising high active and stable non-platinum catalyst for overall water splitting. Highlights: A new preparation, it is first time to fabricate MoS2 /NiCo2 S4 heterostructures. A new morphology and nanostructure with a well tight interface. The MoS2 /NiCo2 S4 hybrid exhibited excellent HER catalytic activity. The MoS2 /NiCo2 S4 exhibited good long-stability in Alkaline Media.